Susceptibility of Trypanosoma evansi in the Copaiba Oil: In Vitro Test and in Mice Experimentally Infected with the Parasite - Fellipe de Souza Dorneles (Acta Scientiae Veterinariae, 2013)
Background: Trypanosoma evansi is a fl agellate which belongs to the salivate section, commonly observed parasitizing blood of equines, ruminants, pigs, dogs and wild animals in different regions of the world. It causes many losses to farmers due to death of animals and drug spending in endemic areas. The treatment of this disease in Brazil is only performed with diminazene aceturate; however it has been ineffective for many animals. During the lats years many studies have been carried out with natural products such as the essential oils. Copaiba oil stands out due some properties described as anti-infl ammatory, healing, antiedematogenic, antitumor, parasitic and antibacterial. Therefore, this study aimed to test, in vitro and in vivo, the susceptibility of T. evansi to copaiba oil. Materials, Methods & Results: The oils used in this study were obtained from Copaifera reticulata and Copaifera duckei trees, commonly found in the Tapajos National Forest. The procedure received authorization of IBAMA due the scientifi c purposes. This study identifi ed three oils identifi ed as copaiba 4-C (C. reticulata), copaiba 5-C (C. duckei) and copaiba 8-C (C. reticulata). The bioassay was performed in vitro using specifi c culture medium for T. evansi, previously described by Baltz, 1985. Copaiba oil was dissolved in dimethyl sulfoxide (DMSO) and tested in three concentrations (0.5, 1.0 and 2.0%) in culture medium containing the parasite. To the control test (without oil) the same volume of DMSO (10 μL) was added. Dimnazene aceturate was also used as a positive control at 0.5% of concentration. The counting of trypanosomes was performed in triplicate in a Neubauer chamber after 1, 3, and 6 hours after the experiment onset. For the tests in vivo, mice were infected (n = 40) and divided in 5 groups of 8 animals each. Group A consisted of healthy animals and Group B comprised animals infected with T. evansi and untreated. The other groups were infected and treated orally with oil of copaíba 4-C (Group C), copaiba 5-C (Group D) and copaiba 8-C (Group E), using a dose of 0.63 mL/kg/day for fi ve consecutive days at intervals of 24 hours. In vitro tests with copaiba oil showed a reduction in the number of alive trypanosomes for the three tested concentrations, when compared to the control test after 1 and 3 h, similar to what occurred with testing aceturate. At 6 hours, it was not observed alive parasites in the test groups, differently from the control group which had an increase of trypanosomes compared to the time zero. The trypanocidal activity had a dose-dependent effect. In the in vivo experiment, the oil of copaiba administered orally had no curative effi cacy for any of the groups; however group D treated with C. duckei showed prolonged longevity of the mice when compared to the groups B and C. Discussion: Trypanosoma cruzi and Leishmania amazonensis have been challenged on their susceptibility to oil of copaiba, with obtention of trypanocidal and leishman